Building Women's Leadership in Education: The Key to Transformation for Lifetime Opportunities and a Success Mindset - Yulia Rahmi Ilmani; Abdul Wahid Zaini; Uswatun Hasanah (Al-Qalam Institute, 2024)
This study aims to analyze the role of women's leadership in education in creating lifelong opportunities and shaping a success mindset. The research method used is a qualitative approach with case study techniques, where data is collected through in-depth interviews with a number of women leaders in educational institutions as well as field observations. The results show that women's leadership has a significant influence in improving the quality of education, shaping a collaborative and resilience-based mindset, and introducing more inclusive policies for students from various backgrounds. The study also found that while gender and social structural challenges still hinder women's participation in educational leadership, appropriate empowerment measures, such as leadership training and increased access to education, could open up greater opportunities for women to play a role in global education transformation. The implication of this study is the importance of designing education policies that support women's leadership as the key to creating a more equitable and sustainable education. This research also contributes to the development of a more inclusive and gender-equality-based educational leadership theory.